The Spillover Effect of Services Offshoring on Local Labour Markets - Martina Magli (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2022)
I provide new empirical evidence on the direct and indirect impact of services offshoring on local employment and wages, using a unique dataset on firms in the UK for the period 2000-2015. Exploiting variation in firms' services offshoring across labour markets, I show positive aggregate local labour employment and wage elasticity to services offshoring. Spillovers from offshoring to non-offshoring firms explain the positive results, and services offshoring complementary to firms' production has a larger effect than the offshoring competing with firms' outputs. Finally, I show that services offshoring widens firms' employment and wage dispersion within local labour markets.
Keywords: F1; F16; J2; 330; services offshoring; local labour market; spillover effect; quantile analysis